Demographic trends and global assessment functioning of intellectually disabled patients admitted in rehabilitations centre Majmaah - Alvi, Tabassum; Hayat, Aalia Akhtar; Sami, Waqas; Farhan, Saira (Progress in Nutrition, 2021)
Background: There is a high prevalence of intellectual disability in Saudi Arabia. Since there is a scarcity of data about the level of functional impairment in people with disability in SA and the association of various demographic variables with the severity of ID, this study was designed to study the various trends in the patients with ID in an inpatient rehabilitative facility in Majmaah, assessing their functionality using GAF and finding any possible association between various variables and severity of ID.Methods: Cross-sectional study was conducted, and Hundred and forty-seven patients were included in the study who were admitted in Rehabilitation center Majmmah and were assessed for demographic and GAF by random sampling variables. Results: Equal number of males and females were found to be in the age range of 11 -44 years. Half of them were bedridden. Seventeen (11.6%) had mild ID, 33 (22.4%) had moderate ID, 56 (38.1 %) had severe ID and 41 (27.9%) had profound ID. The Association of GAF and severity of ID was statistically significant. Conclusions: The study reveals that most of the individuals have GAF score consistent with the level of disability with few discrepancies.